Managing Plant Genetic Diversity. Proceedings of an International Conference, Kuala Lumpur, Malaysia, 12-16 June 2000 2001
DOI: 10.1079/9780851995229.0205
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation dynamics of Lima bean ( Phaseolus lunatus L.) in the Central Valley of Costa Rica.

Abstract: The study of spatial distribution of the population of Lima bean in the Central Valley of Costa Rica showed that for any given population, the mean distance to the nearest population is 1768.7 m (n=497 populations). The range for the distance to the nearest population was between 165 and 3697 m. The occurrence of local population extinction was common in wild populations of Lima bean. A total of 91 episodes of local extinction was recorded, of which, only 19 resulted in permanent loss of the population indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Human activity also creates metapopulation scenarios, e.g. by intensive land use, changes in agricultural practices, and urban development that may result in fragmentation of the landscape and temporal degradation of suitable habitats (Rocha et al . 1997, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Human activity also creates metapopulation scenarios, e.g. by intensive land use, changes in agricultural practices, and urban development that may result in fragmentation of the landscape and temporal degradation of suitable habitats (Rocha et al . 1997, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For each population, we collected a voucher specimen, fruit and seed samples, and described the site with parameters such as size of the population, topography, associated vegetation and geographical coordinates using a Garmin 48 GPS unit. Similar surveys were conducted again in 1993, 1994 and 1999. Previous studies revealed the occurrence of multiple extinction and recolonization events among wild populations of lima beans (Rocha et al 2002, Barrantes 2003. Monthly monitoring of 106 populations for six year (from November 1994 to December 2000) showed that 39 populations experienced local extinction that lasted for more than one year.…”
Section: Study Areamentioning
confidence: 99%
“…These findings suggest that multiple extinctions lead to more severe bottlenecks, hence resulting in more differentiation between samples taken form the same location. Moreover, the likelihood of extinction is also related to population size, as small populations are more likely to disappear (Rocha et al 2002, Barrantes 2003, which suggests that such populations may be more susceptible to genetic losses.…”
Section: Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation